2005
DOI: 10.1590/s1415-47572005000300015
|View full text |Cite
|
Sign up to set email alerts
|

Somaclonal variation in Asparagus officinalis plants regenerated by organogenesis from long-term callus cultures

Abstract: Somaclonal variation in plants regenerated by organogenesis from long-term cultured calluses of two diploid staminate genotypes of Asparagus officinalis cv. Argenteuil was characterized by plant phenotype, ploidy, meiotic behavior, pollen viability, fruit and seed set, and AFLP profiles. Phenotypic deviations from the donors were detected in foliage color, flower size, and cladode and flower morphology. Ploidy changes were observed in 37.8% of the 37 regenerants studied. Meiotic alterations in 12 out of 21 reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 27 publications
3
26
1
Order By: Relevance
“…Application of axillary branches and somatic embryogenesis are better methods for generation of genetically stable clones. However, organogenic differentiation is very prone to somatic variation (Pontaroli and Camadro 2005). Our results demonstrated that since, there were no variations observed among the in vitro conservation media T1, T2 and T3, the most commonly used T2 was considered ideal for in vitro conservation of potato microtubers to generate true-totype plants.…”
Section: Discussionmentioning
confidence: 66%
“…Application of axillary branches and somatic embryogenesis are better methods for generation of genetically stable clones. However, organogenic differentiation is very prone to somatic variation (Pontaroli and Camadro 2005). Our results demonstrated that since, there were no variations observed among the in vitro conservation media T1, T2 and T3, the most commonly used T2 was considered ideal for in vitro conservation of potato microtubers to generate true-totype plants.…”
Section: Discussionmentioning
confidence: 66%
“…The objectives of this study were to (1) assess the type and frequency of somaclonal variation in a caladium cultivar that was widely grown and phenotypically stable, (2) evaluate the effect of two types of explant and auxin on somaclonal variation, and (3) characterize the nuclear DNA content, chromosome number, and molecular marker banding pattern of the obtained somaclonal variants. Experimental data on these aspects of somaclonal variation had been scarce in the aroid family (Raimondi et al 2001;Pontaroli and Camadro 2005). Information gained from this study might also be valuable to other aroids and ornamental plants.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%
“…There are several factors which can influence the ploidy level of the regenerants. Regeneration via organogenesis was said to induce greater variation than in case of somatic embryogenesis (Pontaroli and Camadro 2005). Gaj (2001) showed that all A. thaliana regenerants obtained through somatic embryogenesis were diploids.…”
Section: Ploidy Of Regenerantsmentioning
confidence: 99%